Manifestations of the biblical narrative in the poetry of Mahmoud Darwish - Keadan, Rasmiya Youssef; Al-Deek, Ihsan (Journal of Arabic Language Sciences and Literature, 2024)
The research concluded that Mahmud Darwish’s interest in the biblical narrative in his poems and writings came to enrich Darwish’s poetic experience, whether he was Darwish the poet or Darwish the politician. The biblical narrative is full of traditional symbols that greatly helped Darwish to employ their symbols in writing his poetic verses. The research reached several results, including the following: 1. Mahmoud Darwish’s interest in the biblical narrative in his poems and writings came to enrich his poetic experience, whether he was Darwish the poet or Darwish the politician. The biblical narrative is full of traditional symbols that greatly helped Darwish to employ their symbols in writing his poetic verses. 2. The myths that appeared in Mahmoud Darwish’s poetry are the myth of the Promised Land, the land of God’s chosen people, and the myth of the alleged Temple, with whose presence the Israeli presence on the land of Palestine is linked. 3. The myths show us that the alleged Israeli state is based on traditional religious claims, and that the Zionist movement calls for the revival of the national homeland for the Jews on the land of Palestine, that is, the Promised Land for them. The research recommends the following: 1. Studying the influence of the biblical novel on Mahmoud Darwish’s poems, where it is possible to explore how Darwish’s poems were influenced by the stories, symbols and values present in the biblical novel, and a comparison between the cultural and religious elements in the novel and their manifestations in Darwish’s poetry. 2. Analysis of religious concepts in Mahmoud Darwish’s poetry, where it is possible to explore how Darwish used religious symbols and concepts from the biblical narrative in his poems, and search for the significance of religious symbols and concepts in his poetry and their impact on its content and form.
Keywords: Mahmud Darwish; the biblical novel; Arabic poetry; Jewish poetry